Modelos de governo, gerencialismo e avaliação institucional nas universidades - Rui A. Santiago; Denise Leite; Marlis Polidori; Maria Cecília Leite Loréa; Claúdia Sarrico (Universidade do Minho, 2003)
In this article we intend to discuss the relation between different universitysgovernance models, institutional assessment and new managerialism. First,we analyse the meaning given to institutional assessment in the rationalitymodel, the ambiguity and uncertainty model and the political model. In asecond moment, we will look at the influence of the new managerialism inuniversitys governance and in the institutional assessment as expressions ofthe attempts to introduce the market notion in higher education. Theseattempts have contributed to the rise of a new technical bureaucratic rationalitywhich is surpassing the substantive rationality that characterises the academicactivities, strongly influencing the internal universitys governance system.